(untitled) (PANGEEA, 2025)
The abuse and neglect of children continue to be two sensitive subjects of the public agenda, on which the attention and efforts of the authorities, but also those of the relevant actors from the non-governmental environment, will continue to be directed with the same concern. The need to harmonize this common effect must remain a priority, given the serious long-term effects that acts of violence perpetrated on a child can have on his future development and his behavior as an adult, in the overall rules of social coexistence. The relevant and substantial analysis of the various forms that violence against children takes, at the level of Romanian society, brings to the fore the way in which children and adults perceive the phenomenon of violence, its consequences or the causalities underlying such behavior. The phenomenon of abuse still has a weak recognition and awareness at the level of society. The specific cultural paternal gives the family a closed status, the process of collective awareness of situations of abuse being just at the beginning.